Activation of Transition Metal (Fe, Co and Ni)‐Oxide Nanoclusters by Nitrogen Defects in Carbon Nanotube for Selective CO2 Reduction Reaction. Issue 1 (22nd March 2022) - Cheng, Yi; Chen, Jinfan; Yang, Chujie; Wang, Huiping; Johannessen, Bernt; Thomsen, Lars; Saunders, Martin; Xiao, Jianping; Yang, Shize; Jiang, San Ping
Abstract : The electrochemical carbon dioxide reduction reaction (CO2 RR), which can produce value‐added chemical feedstocks, is a proton‐coupled‐electron process with sluggish kinetics. Thus, highly efficient, cheap catalysts are urgently required. Transition metal oxides such as CoO x, FeO x, and NiO x are low‐cost, low toxicity, and abundant materials for a wide range of electrochemical reactions, but are almost inert for CO2 RR. Here, we report for the first time that nitrogen doped carbon nanotubes (N‐CNT) have a surprising activation effect on the activity and selectivity of transition metal‐oxide (MO x where M = Fe, Ni, and Co) nanoclusters for CO2 RR. MO x supported on N‐CNT, MO x /N‐CNT, achieves a CO yield of 2.6–2.8 mmol cm −2 min −1 at an overpotential of −0.55 V, which is two orders of magnitude higher than MO x supported on acid treated CNTs (MO x /O‐CNT) and four times higher than pristine N‐CNT. The faraday efficiency for electrochemical CO2 ‐to‐CO conversion is as high as 90.3% at overpotential of 0.44 V. Both in‐situ XAS measurements and DFT calculations disclose that MO x nanoclusters can be hydrated in CO2 saturated KHCO3, and the N defects of N‐CNT effectively stabilize these metal hydroxyl species under carbon dioxide reduction reaction conditions, which can split the water molecules and provide local protons to inhibit the poisoning of active sites under carbon dioxide reduction reaction conditions. Abstract : The nitrogen defects on the carbon nanotubes can activate the non‐active transition metal oxide nanoclusters for carbon dioxide reduction. The origin of activity is attributed to the nitrogen defects in carbon nanotubes which can stabilize the metal oxide/hydroxide nanoclusters, that prevents them from being reduced at reduction potentials under carbon dioxide reduction condition, and thus provides local protons to assist the carbon dioxide reduction.